What Is Culturally Informed Literacy Instruction? A Review of Research in P–5 Contexts. (March 2021) - Kelly, Laura Beth; Wakefield, Wendy; Caires-Hurley, Jaclyn; Kganetso, Lynne Watanabe; Moses, Lindsey; Baca, Evelyn
This critical, integrative qualitative review explores how researchers approach, describe, and justify culturally relevant, culturally responsive, or culturally sustaining literacy instruction in prekindergarten through fifth-grade (P–5) classrooms. We reviewed 56 studies published between 1995 and 2018. We documented terms researchers use, theorists cited, methods, student outcomes, and student populations. We also analyzed how researchers talked about achievement gaps, addressed their own positionality, and determined that specific literacy instructional practices were culturally informed. We found that researchers most commonly claim to document culturally relevant or responsive instruction, in some cases conflating the terms and related theorists. Most studies were qualitative, occurred with traditionally marginalized students (usually Black or Latinx) in the United States, and involved students reading a text that researchers deem culturally informed. We make recommendations for teachers and researchers to move the field of culturally informed literacy forward.